How enjoyment affects English acquisition and anxiety for university students: An analytical study - Khan, Shahzad Dilshad; Mohammed, Lubna Ali; Mustafa, Muhammad (Yayasan Mitra Persada Nusantara, 2024)
One of the main aims of foreign language (FL) teaching is to prepare students to speak the target language. Therefore, teachers need to help students develop communication skills. However, this ability only sometimes leads to theforeign language anxiety (FLA). The study aims to analyze the counter-effect of enjoyment of a foreign language (FLE) on the relationship between anxiety and the acquisition of English as a foreign language among university students. A quantitative research method is used to identify the relationship between foreign languages and anxiety. The expected results shown negative impact of enjoyment of a foreign language on anxiety, a negative impact of acquiring a foreign language(AFL) on anxiety, and a positive relationship between FLE and efficiency. The expected findings posited that anxiety is a negative emotion in psychology as it destroys students’ mental health to learn a foreign language. On the other hand, positive emotions contribute to student well-being and increase student motivation and the learning language process.